Introduction of Specialized Rehabilitation Services in the Family Type Hotel - Рольська, Роксолана Вікторівна; Шаран, Лариса Олександрівна; Бондар, Наталя Петрівна; Губеня, В’ячеслав Олександрович (Київський національний університет імені Тараса Шевченка, 2019)
Purpose. The purpose of the article is to justify the feasibility of introducing specialized packages with rehabilitation services for children with special needs in a family-type hospitality establishment. Indeed, statistics show that in recent years in Ukraine and the world the number of cases of autism is increasing. Methodology. The methodological basis of this work is the work of domestic and foreign scientists in the field of inclusion, scientific periodicals, Internet resources. The methodology includes statistical data of the State Statistics Service of Ukraine and others, which reflect the prevalence of psychophysical diseases and their number. The methodology also includes the work of foreign scientists on the evidence of the effectiveness of a special diet. Results. As a result of the research, world experience was analyzed regarding the introduction in Ukraine of comfortable conditions for rehabilitation, as well as relaxation in institutions for placement of family-type children with special needs. It was revealed that in our country there is no experience in introducing such services in hotels. Specialized services for children have been developed that can be implemented in an innovative placement institution. The results will help move the problem of effective specialized rehabilitation of children with autism in combination with quality rest. Scientific novelty. The necessity of introducing services for the rehabilitation of children with developmental disabilities is identified. The world experience is systematized regarding the introduction of comfortable conditions for rest and rehabilitation in hotel complexes of children with autism in Ukraine with an analysis of the available methods for the possibility of their application in the development of the hotel business. Specialized services are provided that will enhance the institution's competitiveness, as well as allow families with special children to travel, relax and improve their health. Practical significance. Coverage of the problem of providing specialized rehabilitation services for children in Ukraine and the development of practical ways to solve it will improve the situation in the hotel market of the country. In the future, packages of services that can be used in hospitals by specialists for working with special children will be developed. This will lead to the development of wellness programs for children, involving classes by specially trained personnel, while parents will be able to devote their free time to outdoor recreation. The introduction of such services will help to increase public awareness, as well as the development of inclusion.

Мета. Метою статті є обґрунтування доцільності впровадження спеціалізованих пакетів із реабілітаційними послугами для дітей, які мають особливі потреби у закладі гостинності сімейного типу. Адже статистика свідчить, що за останні роки в Україні та світі кількість випадків аутизму зростає. Методика. В якості методичної основи даної роботи виступають роботи вітчизняних та закордонних науковців у сфері інклюзії, наукова періодика, ресурси мережі Інтернет. В методику входять статистичні дані Державної служби статистики України та ін., де відображено поширеність психофізичних захворювань та їх чисельність. Методика також включає роботи іноземних науковців про доведеність дієвості спеціальної дієти. Результати. У результаті досліджень було проаналізовано світовий досвід щодо впровадження в Україні комфортних умов для реабілітації, а також відпочинку в закладах розміщення сімейного типу дітей з особливими потребами. Виявлено, що у нашій державі ще немає досвіду впровадження таких послуг у готелях. Було розроблено спеціалізовані послуги для дітей, які можуть бути реалізовані в інноваційному закладі розміщення. Результати допоможуть зрушити з місця проблему ефективної спеціалізованої реабілітації дітей з аутизмом у поєднанні з якісним відпочинком. Наукова новизна. Визначено необхідність впровадження послуг для реабілітації дітей з особливостями розвитку. Систематизовано світовий досвід щодо впровадження в Україні комфортних умов для відпочинку та реабілітації у готельних комплексах дітей з аутизмом із аналізом наявних методів на можливість їхнього застосування в розвитку готельного бізнесу. Наведено спеціалізовані послуги, які сприятимуть підвищенню конкурентоспроможності закладу, а також дадуть змогу сім’ям з особливими дітьми якісно подорожувати, відпочивати та оздоровлюватись. Практична значимість. Висвітлення проблеми надання спеціалізованих реабілітаційних послуг для дітей в Україні та розроблення практичних шляхів її вирішення покращить ситуацію на готельному ринку країни. Надалі розроблятимуться пакети послуг, які можуть застосовуватися у закладах гостинності спеціалістами для роботи з особливими дітьми. Це призведе до розробки оздоровчих програм для дітей, що передбачатимуть заняття зі спеціально підготовленим персоналом, тоді як батьки зможуть присвятити вільний час відпочинку на природі. Впровадження таких послуг сприятиме підвищенню свідомості суспільства, а також розвитку інклюзії.
Впровадження спеціалізованих реабілітаційних послуг у готелі сімейного типу
Keywords: готель сімейного типу; спеціалізовані послуги; реабілітація; діти з особливими потребами; family-type hotel; specialized services; rehabilitation; children with special needs